2022
DOI: 10.1016/j.aninu.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of barley inclusion method and protease supplementation on growth performance, nutrient utilisation, and gastrointestinal tract development in broiler starters

Abstract: The influence of the method of barley inclusion (fine, coarse and whole barley) in a wheat-based diet and protease supplementation (0 and 0.20 g/kg) on growth performance, nutrient utilisation and gastrointestinal tract development of broilers (d 1 to 21) was evaluated in a 3 × 2 factorial arrangement. Whole barley (WB) grains were ground in a hammer mill to pass through the screen sizes of 2.5 and 8.0 mm to achieve fine (FB) and coarse (CB) barley particle sizes, respectively. A total of 288, one-day-old male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 61 publications
3
11
0
Order By: Relevance
“…Interestingly, our research shows that there were no significant differences in broilers BW and BWG and nutrient digestibility between supplementation of enzymes and probiotics, compared with the newly harvested corn diet group. This is consistent with the findings of Hussein et al (2020) [ 34 ], Al-Khalaifa et al (2019) [ 18 ], and Tari et al (2022) [ 35 ]. This result may be related to the good balance of digestible amino acids and the high inherent protein digestibility in the basal diet and complex changes in digestive enzyme activities.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our research shows that there were no significant differences in broilers BW and BWG and nutrient digestibility between supplementation of enzymes and probiotics, compared with the newly harvested corn diet group. This is consistent with the findings of Hussein et al (2020) [ 34 ], Al-Khalaifa et al (2019) [ 18 ], and Tari et al (2022) [ 35 ]. This result may be related to the good balance of digestible amino acids and the high inherent protein digestibility in the basal diet and complex changes in digestive enzyme activities.…”
Section: Discussionsupporting
confidence: 93%
“…However, Perera et al [ 149 ] reported that starch digestibility in broilers fed barley-based diets was not influenced by barley particle size. In agreement, Tari et al [ 151 ] reported no influence of the method of barley inclusion (fine, coarse and WB) in wheat-based diets on starch utilisation. Enhanced starch digestibility may also be attributed to mechanisms facilitated by well-developed gizzards.…”
Section: Barley In Poultry Nutritionsupporting
confidence: 61%
“…Enhanced starch digestibility may also be attributed to mechanisms facilitated by well-developed gizzards. However, no impact on the starch digestibility was reported despite functional gizzards in birds fed coarse [ 149 ] and WB [ 151 ]. On the other hand, a recent study [ 152 ] reported an enhanced starch digestibility in response to increasing the WB inclusions from 0 to 141 and 282 by 3.6 and 5.7%, respectively, despite the lack of impact on gizzard size.…”
Section: Barley In Poultry Nutritionmentioning
confidence: 99%
See 2 more Smart Citations